Long-shelf-life high-strength two-component polyurethane structural adhesive for power battery and preparation method of long-shelf-life high-strength two-component polyurethane structural adhesive
By using raw materials such as bio-based polyols and aromatic ring-modified polyols in the two-component polyurethane structural glue for power batteries, combined with terminal isocyanate-based polyurethane prepolymers, the problems of low strength and poor storage stability in the prior art are solved, and adhesives with high strength, long shelf life and good stability are achieved, which are suitable for use in complex environments of power batteries.
Patent Information
- Application Number
- CN202411906077.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing polyurethane structural glue has problems of low strength and poor storage stability during storage and transportation, especially the B component is prone to thickening and crust under long-term storage or improper transportation environments, which affects the structural bonding performance.
A two-component polyurethane structural glue for high-strength power batteries with a long shelf life is used. The A component consists of bio-based polyols, aromatic ring-modified polyols and aromatic ring-containing polyether polyols. The B component consists of terminal isocyanate-based polyurethane prepolymers and anti-hydrolyzers. The molar ratio of functional groups is NCO:OH=1.05:1~2.0:1. Terminate isocyanate-based prepolymers are prepared by partially carboxy-terminated polyester polyols modified with anhydride, which extends the opening time of component B and improves the stability and strength of the adhesive.
The high strength, long shelf life and good storage stability of two-component polyurethane structural adhesive is achieved, and the opening time of component B is extended. It is suitable for the high-frequency vibration and humid and heat aging environment of power batteries, ensuring the long-term use stability and safety of power batteries in complex environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane structural adhesive for batteries, and in particular to a two-component polyurethane structural adhesive for high-strength power batteries with a long shelf life and a preparation method thereof. Background Art
[0002] At present, with the development of the times, the use of cars is increasing, various problems have emerged, and the situation is severe. New energy electric vehicles are a mainstream trend to solve energy, environment, urban transportation and other problems, and are also a major direction for the development of the future automobile industry. As a power battery that provides power for new energy vehicles, it is an indispensable core component of new energy vehicles and is directly related to important performance such as the vehicle's endurance, power, life, safety and power consumption.
[0003] The power batteries used in new energy vehicles are currently composed of multiple cells connected in series and / or in parallel. With the innovation of power battery assembly technology, the technology of improving energy density and de-modularization has received more and more attention. In this process, more and more metal structural parts are replaced by adhesives, and the amount of adhesive used continues to increase. Moreover, with the continuous increase in the sales volume and installation volume of power batteries, adhesives have become one of the key factors to achieve stable, safe, efficient and long-lasting operation of power battery electric drive systems.
[0004] Two-component polyurethane adhesives have become the first choice due to their high storage stability, excellent electrical insulation, easy modulus adjustment, safety, environmental protection and high reliability. During the driving process of the car, the structural bonding of two-component polyurethane adhesives must have the ability to buffer high-frequency vibrations and resist aging, and should also meet the excellent bonding ability for materials such as Al, steel, PET, PC and alloys. However, the mainstream polyurethane structural adhesives on the market currently face the problems of low strength and poor storage stability, especially component B. If the storage time is too long or the transportation environment such as export sea transportation is not appropriate, problems such as thickening and crusting will occur, affecting the performance of structural bonding.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a two-component polyurethane structural adhesive for high-strength power batteries with a long shelf life and a preparation method thereof, which can extend the open time of component B, improve the shelf life of the two-component polyurethane structural adhesive for high-strength power batteries, and maintain high strength, thereby solving the above-mentioned technical problems existing in the prior art.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, comprising:
[0009] Component A and component B, the functional group molar ratio of component A to component B is: NCO:OH=1.05:1-2.0:1, and the component A and component B are mixed in a volume ratio of 1:1; wherein,
[0010] The component A is composed of the following raw materials by mass fraction: 20% to 40% of a first bio-based polyol, 5% to 15% of a second bio-based polyol, 2% to 30% of an aromatic ring-modified polyol, 5% to 20% of an aromatic ring-containing polyether polyol, 0.5% to 1.5% of a coupling agent, 0.01% to 0.5% of a catalyst, 10% to 40% of a flame retardant, 2% to 10% of a dehumidifier, 0.1% to 0.5% of an antioxidant, and 0.5% to 5% of a thixotropic agent;
[0011] The B component is composed of the following raw materials by mass fraction: 60% to 85% of terminal isocyanate polyurethane prepolymer, 10% to 40% of flame retardant, 0.5% to 5% of thixotropic agent, 0.1% to 0.5% of dehydrating agent and 0.1% to 1% of anti-hydrolysis agent.
[0012] Preferably, in the component A of the structural adhesive, the first bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic ring-modified castor oil;
[0013] The second bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic ring-modified castor oil;
[0014] The aromatic ring modified polyol is one or more of bisphenol A or bisphenol F modified polyether diol and phthalic anhydride polyester diol with a molecular weight of 400 to 3000;
[0015] The hydroxyl value of the aromatic ring-containing polyether polyol is 150 mg KOH / g to 450 mg KOH / g;
[0016] The coupling agent is one or more of silane coupling agents KH550, KH560, KH570, KH580, and KH792;
[0017] The catalyst is one or more of N,N-dimethylcyclohexylamine, triethylenediamine, 1,2-dimethylimidazole, N-ethylmorpholine, N-methylmorpholine, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth naphthenate, zinc isooctanoate, zinc neodecanoate, dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, and chelated tin;
[0018] The dehydrating agent is one or more of molecular sieve, calcium chloride and aluminum sulfate;
[0019] The antioxidant is one or more of 1076, 1010, 1135 and 245.
[0020] Preferably, in the component B of the structural adhesive, the isocyanate-terminated polyurethane prepolymer is produced by reacting an anhydride-modified partially carboxyl-terminated polyester polyol with a molecular weight of 500-4000 with isocyanate, and the mass fraction of NCO is controlled to be 5-20%.
[0021] Preferably, in the above structural adhesive, in the isocyanate-terminated polyurethane prepolymer, the isocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and liquefied MDI;
[0022] The anhydride-modified partially carboxyl-terminated polyester polyol is a polyester polyol synthesized from a diacid monomer and a polyol monomer.
[0023] Preferably, in the above structural adhesive, in the acid anhydride-modified partially carboxyl-terminated polyester polyol, the diacid monomer is one or more of hydrogenated dimer acid, dimer acid, succinic acid, adipic acid, sebacic acid, terephthalic acid, isophthalic acid, and phthalic anhydride;
[0024] The acid anhydride is one or more of maleic anhydride, succinic anhydride, glutaric anhydride, phthalic anhydride, tetrahydrophthalic anhydride, bromotetrahydrophthalic anhydride, and hexahydrophthalic anhydride;
[0025] The polyol monomer is one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,10-decanediol, glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0026] Preferably, in the component B of the structural adhesive, the anti-hydrolysis agent is polycarbodiimide;
[0027] The dewatering agent is p-toluenesulfonyl isocyanate.
[0028] Preferably, in the structural adhesive, in the component A and the component B, the thixotropic agent is one or more of fumed silica and bentonite;
[0029] In the component A and the component B, the flame retardant is a solid flame retardant or a liquid flame retardant.
[0030] Preferably, in the above structural adhesive, the solid flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, and aluminum diethylphosphite;
[0031] The liquid flame retardant is one or more of tricresyl phosphate, triethyl phosphate, and tri(chloroisopropyl) phosphate.
[0032] A two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life according to the present invention comprises the following steps:
[0033] According to the formula of component A and component B of the present invention, the constituent raw materials of component A and component B are respectively taken, and the raw materials of component A and component B are respectively mixed evenly to obtain component A and component B, and the prepared component A and component B are combined and used in a volume ratio of 1:1 to obtain a high-strength two-component polyurethane structural adhesive for power batteries with a long shelf life.
[0034] Preferably, in the above preparation method, the isocyanate-terminated polyurethane prepolymer in component B is prepared in the following manner, including:
[0035] First, prepare anhydride-modified partially carboxyl-terminated polyester polyol as follows:
[0036] Adding polyester polyol and acid anhydride into a reaction container, adding in a molar ratio of acid anhydride to hydroxyl group in terminal hydroxyl polyester polyol of 1:100 to 1:5, heating polyester polyol and acid anhydride to 100-200° C., stirring for 2-6 hours, until the chemical titration result of hydroxyl value and acid value is less than 5% of the theoretical error, ending the reaction, cooling to room temperature, and obtaining acid anhydride-modified partially carboxyl-terminated polyester polyol;
[0037] The isocyanate-terminated prepolymer is then prepared in the following manner, comprising:
[0038] The anhydride-modified partially carboxyl-terminated polyester polyol is heated to 110-120° C., stirred and vacuumed, dehydrated for 1-3 hours, cooled to below 50° C., filled with nitrogen, and isocyanate is added in a ratio of 5-20% of the theoretical NCO content. The temperature is raised to 65-85° C., stirred and reacted for 1-5 hours until the titrated NCO content no longer changes to terminate the reaction, and cooled to room temperature to obtain an isocyanate-terminated prepolymer.
[0039] Compared with the prior art, the two-component polyurethane structural adhesive for high-strength power batteries with a long shelf life and the preparation method thereof provided by the present invention have the following beneficial effects:
[0040] By adding aromatic ring modified polyols and aromatic ring-containing polyether polyols to component A, the rigidity of the molecular chain is improved, the glass transition temperature is increased, the heat resistance is improved, and the bonding strength to PET and metal substrates is effectively improved; by adding bio-based polyols to component A and dimer acid-based polyester polyols to component B, the hydrophobicity of the molecular chain and the resistance to wet and hot aging can be improved, and the flexibility of the molecular chain can be increased, a high elongation can be maintained, and the molecular chain can be promoted to form a microphase separation structure after polyurethane curing, which is beneficial to maintaining high mechanical properties. By adding the end-isocyanate polyurethane prepolymer prepared by partially carboxyl-terminated polyester polyols modified by acid anhydride to component B, the reaction rate of isocyanate with water molecules in the air can be effectively slowed down, so that the open time of component B is greatly extended, and the stability of component B during storage and transportation is effectively improved. Compared with the prior art, the two-component polyurethane structural adhesive of the present invention has the following characteristics: (1) higher strength, with a bulk tensile strength of ≥10MPa, and a shear strength of ≥10MPa for substrates such as PET, PC, aluminum alloy, and steel, ensuring safety and reliability during driving. (2) excellent resistance to wet and hot aging, with a tensile strength and shear strength decay of <10% after aging at 85° for 1000h. (3) a longer open time for component B, which is ≥15h under standard conditions. DETAILED DESCRIPTION
[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in combination with the specific content of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, which does not constitute a limitation of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0042] First, the terms that may be used in this article are explained as follows:
[0043] The term “and / or” means that either or both of them can be realized at the same time. For example, X and / or Y means both “X” or “Y” and “X and Y”.
[0044] The terms "include", "comprises", "contains", "has" or other descriptions with similar semantics should be interpreted as non-exclusive inclusion. For example, including certain technical feature elements (such as raw materials, components, ingredients, carriers, dosage forms, materials, dimensions, parts, components, mechanisms, devices, steps, procedures, methods, reaction conditions, processing conditions, parameters, algorithms, signals, data, products or products, etc.) should be interpreted as including not only certain technical feature elements explicitly listed, but also other technical feature elements known in the art that are not explicitly listed.
[0045] The term "consisting of..." means excluding any technical feature elements not explicitly listed. If this term is used in a claim, it will make the claim closed, so that it does not contain technical feature elements other than the technical feature elements explicitly listed, except for the conventional impurities related to them. If this term only appears in a clause of a claim, it only limits the elements explicitly listed in the clause, and the elements recorded in other clauses are not excluded from the overall claim.
[0046] The term "parts by mass" refers to the mass ratio relationship between multiple components. For example, if it is described that component X is x parts by mass and component Y is y parts by mass, then the mass ratio of component X to component Y is x:y. 1 part by mass can represent any mass, for example, 1 part by mass can be represented as 1 kg or 3.1415926 kg. The sum of the parts by mass of all components is not necessarily 100 parts, but can be greater than 100 parts, less than 100 parts or equal to 100 parts. Unless otherwise specified, the parts, proportions and percentages described herein are all measured by mass.
[0047] Unless otherwise specified or limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this article can be understood according to specific circumstances.
[0048] When concentration, temperature, pressure, size or other parameters are expressed in the form of a numerical range, the numerical range should be understood to specifically disclose all ranges formed by the pairing of any upper limit, lower limit, and preferred value in the numerical range, regardless of whether the range is explicitly stated; for example, if a numerical range of "2 to 8" is stated, the numerical range should be interpreted as including ranges such as "2 to 7", "2 to 6", "5 to 7", "3 to 4 and 6 to 7", "3 to 5 and 7", "2 and 5 to 7", etc. Unless otherwise specified, the numerical ranges stated herein include both their end values and all integers and fractions within the numerical range.
[0049] The orientation or position relationship indicated by terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", etc. are based on the orientation or position relationship shown and are only for the convenience of description and simplification of description, and do not explicitly or implicitly indicate that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore should not be understood as a limitation of this document.
[0050] The scheme provided by the present invention is described in detail below. The contents not described in detail in the embodiments of the present invention belong to the prior art known to professionals in the field. If the specific conditions are not specified in the embodiments of the present invention, they are carried out according to the conventional conditions in the field or the conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used in the embodiments of the present invention, they are all conventional products that can be purchased commercially.
[0051] The embodiment of the present invention provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, comprising:
[0052] The molar ratio of functional groups of component A and component B is: NCO:OH=1.05:1-2.0:1, and the component A and component B are mixed in a volume ratio of 1:1;
[0053] The component A is composed of the following raw materials by mass fraction: 20-40 parts of the first bio-based polyol, 5-15 parts of the second bio-based polyol, 2-30 parts of the aromatic ring-modified polyol, 5-20 parts of the aromatic ring-containing polyether polyol, 0.5-1.5 parts of the coupling agent, 0.01-0.5 parts of the catalyst, 10-40 parts of the flame retardant, 2-10 parts of the dehydrating agent, 0.1-0.5 parts of the antioxidant and 0.5-5 parts of the thixotropic agent;
[0054] The B component is composed of the following raw materials by mass fraction: 60-85 parts of terminal isocyanate polyurethane prepolymer, 10-40 parts of flame retardant, 0.5-5 parts of thixotropic agent, 0.1-0.5 parts of water remover and 0.1-1 parts of anti-hydrolysis agent.
[0055] Preferably, in the component A of the structural adhesive, the first bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic-modified castor oil.
[0056] The second bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic ring-modified castor oil.
[0057] The aromatic ring modified polyol is one or more of bisphenol A or bisphenol F modified polyether diol with a molecular weight of 400 to 3000, or phthalic anhydride polyester diol.
[0058] The hydroxyl value of the aromatic ring-containing polyether polyol is 150 mg KOH / g to 450 mg KOH / g.
[0059] Preferably, in component A of the above structural adhesive, the coupling agent is one or more of the silane coupling agents KH550, KH560, KH570, KH580, and KH792.
[0060] The catalyst is one or more of N,N-dimethylcyclohexylamine, triethylenediamine, 1,2-dimethylimidazole, N-ethylmorpholine, N-methylmorpholine, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth cycloalkaneate, zinc isooctanoate, zinc neodecanoate, dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, and chelated tin.
[0061] Preferably, in the component A of the structural adhesive, the dehydrating agent is one or more of molecular sieve, calcium chloride and aluminum sulfate;
[0062] Preferably, in component A of the above structural adhesive, the flame retardant is one or more of solid flame retardants such as aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, diethyl aluminum phosphite, and liquid flame retardants such as tricresyl phosphate, triethyl phosphate, tri(chloroisopropyl) phosphate.
[0063] Preferably, in the component A of the structural adhesive, the dehydrating agent is one or more of molecular sieve, calcium chloride and aluminum sulfate;
[0064] The antioxidant is one or more of 1076, 1010, 1135 and 245.
[0065] Preferably, in the component B of the structural adhesive, the isocyanate-terminated polyurethane prepolymer is produced by reacting an anhydride-modified partially carboxyl-terminated polyester polyol with a molecular weight of 500-4000 with isocyanate, and the mass fraction of NCO is controlled to be 5-20%.
[0066] Preferably, in the above-mentioned isocyanate-terminated polyurethane prepolymer, the isocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and liquefied MDI.
[0067] Preferably, in the above-mentioned isocyanate-terminated polyurethane prepolymer, the anhydride-modified partially carboxyl-terminated polyester polyol is a polyester polyol synthesized from a diacid monomer and a polyol monomer. The acid anhydride is one or more of maleic anhydride, succinic anhydride, glutaric anhydride, phthalic anhydride, tetrahydrophthalic anhydride, bromotetrahydrophthalic anhydride, and hexahydrophthalic anhydride; the diacid monomer is one or more of hydrogenated dimer acid, dimer acid, succinic acid, adipic acid, sebacic acid, terephthalic acid, isophthalic acid, and phthalic anhydride; and the polyol monomer is one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,10-decanediol, glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0068] Preferably, in the above-mentioned component B, the flame retardant is one or more of solid flame retardants such as aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, diethyl aluminum phosphite, and liquid flame retardants such as tricresyl phosphate, triethyl phosphate, tri(chloroisopropyl) phosphate.
[0069] Preferably, in the above-mentioned component B, the anti-hydrolysis agent is polycarbodiimide;
[0070] The dewatering agent is p-toluenesulfonyl isocyanate.
[0071] The present invention also provides a method for preparing the above-mentioned two-component polyurethane structural adhesive for a long shelf life and high-strength power battery, comprising the following steps:
[0072] According to the above formula of component A and component B, the constituent raw materials of component A and component B are respectively taken, and the raw materials of component A and component B are respectively mixed evenly to obtain component A and component B, and the prepared component A and component B are combined and used in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0073] Preferably, in the above preparation method, the isocyanate-terminated polyurethane prepolymer in component B is prepared in the following manner, including:
[0074] First, prepare anhydride-modified partially carboxyl-terminated polyester polyol as follows:
[0075] Adding polyester polyol and acid anhydride into a reaction container, adding in a molar ratio of acid anhydride to hydroxyl group in terminal hydroxyl polyester polyol of 1:100 to 1:5, heating polyester polyol and acid anhydride to 100-200° C., stirring for 2-6 hours, until the chemical titration result of hydroxyl value and acid value is less than 5% of the theoretical error, ending the reaction, cooling to room temperature, and obtaining acid anhydride-modified partially carboxyl-terminated polyester polyol;
[0076] The isocyanate-terminated prepolymer is then prepared in the following manner, comprising:
[0077] The anhydride-modified partially carboxyl-terminated polyester polyol is heated to 110-120° C., stirred and vacuumed, dehydrated for 1-3 hours, cooled to below 50° C., filled with nitrogen, and isocyanate is added in a ratio of 5-20% of the theoretical NCO content. The temperature is raised to 65-85° C., stirred and reacted for 1-5 hours until the titrated NCO content no longer changes to terminate the reaction, and cooled to room temperature to obtain an isocyanate-terminated prepolymer.
[0078] In summary, the two-component polyurethane structural adhesive of the embodiment of the present invention does not contain solvents, has good storage stability, component B has a long open time, and has a suitable and adjustable post-mixing operation time, and has excellent bonding properties for substrates such as aluminum, steel, PC, and PET, high strength, strong flame retardant properties, and excellent resistance to moisture and heat aging, and can meet the performance requirements of power battery PACK adhesives. The present invention solves the problem of low strength and poor storage stability of existing structural adhesives.
[0079] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the solution provided by the embodiment of the present invention is described in detail with specific embodiments below.
[0080] Example 1
[0081] This embodiment provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, and a preparation method thereof includes:
[0082] Preparing an isocyanate-terminated polyurethane prepolymer in advance, wherein the isocyanate-terminated prepolymer and each raw material are calculated by weight;
[0083] (1) Preparation of terminal isocyanate prepolymer: 50 parts of poly(hexamethylene dimer) with a molecular weight of 2000-3000 are taken, heated to 120°C while stirring, vacuumed and dehydrated for 2 hours, cooled to 40°C, filled with nitrogen, added with 50 parts of liquefied MDI, slowly heated to 80°C, stirred for reaction for 2 hours, and cooled to room temperature to obtain terminal isocyanate prepolymer;
[0084] Then, component A and component B are prepared respectively, wherein each raw material in component A and component B is calculated by weight;
[0085] (3) Preparation of component A: 40 parts of hydrogenated castor oil polyol, 8 parts of soybean oil, 5 parts of bisphenol A modified polyol, 12 parts of polyether polyol containing aromatic ring, 1.0 part of KH560, 0.2 parts of dibutyltin dilaurate, 30 parts of aluminum hydroxide, 5 parts of molecular sieves, 1.5 parts of fumed silica, and 0.5 parts of 1135 were dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0086] (4) Preparation of component B: 70 parts of isocyanate-terminated prepolymer, 30 parts of aluminum hydroxide, 0.5 parts of p-toluenesulfonyl isocyanate, 1.5 parts of fumed silica, and 0.5 parts of polycarbodiimide were taken, and stirred for 2 hours to obtain component B;
[0087] (5) The component A and the component B prepared above are combined in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0088] Example 2
[0089] This embodiment provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, and a preparation method thereof includes:
[0090] Preparing anhydride-modified partially carboxyl-terminated polyester polyol in advance, and then preparing isocyanate-terminated polyurethane prepolymer, wherein the isocyanate-terminated prepolymer and each raw material are calculated by mass fraction;
[0091] (1) Preparing an anhydride-modified partially carboxyl-terminated polyester polyol, comprising: taking phthalic anhydride and poly(hexamethylene dimer) with a molecular weight of 2000-3000, adding them in a molar ratio of anhydride to hydroxyl groups in the hydroxyl-terminated polyester polyol of 1:100, heating the polyester polyol and the anhydride to 150° C., stirring for 4 hours, until the error between the chemical titration result of the hydroxyl value and the acid value and the theoretical value is less than 5%, terminating the reaction, and cooling to room temperature to obtain an anhydride-modified partially carboxyl-terminated polyester polyol.
[0092] (2) Take 50 parts of anhydride-modified partially carboxyl-terminated polyester polyol, stir and heat to 120°C, maintain vacuum to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 50 parts of liquefied MDI, slowly heat to 80°C, stir to react for 2 hours, and cool to room temperature to obtain a terminal isocyanate prepolymer.
[0093] Then, component A and component B are prepared respectively, wherein each raw material in component A and component B is calculated by weight;
[0094] (3) Preparation of component A: 40 parts of hydrogenated castor oil polyol, 8 parts of soybean oil, 5 parts of bisphenol A modified polyol, 12 parts of polyether polyol containing aromatic ring, 1.0 part of KH560, 0.2 parts of dibutyltin dilaurate, 30 parts of aluminum hydroxide, 5 parts of molecular sieves, 1.5 parts of fumed silica, and 0.5 parts of 1135 were dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0095] (4) Preparation of component B: 70 parts of isocyanate-terminated prepolymer, 30 parts of aluminum hydroxide, 0.5 parts of p-toluenesulfonyl isocyanate, 1.5 parts of fumed silica, and 0.5 parts of polycarbodiimide were taken, and stirred for 2 hours to obtain component B;
[0096] (5) The component A and the component B prepared above are combined in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0097] Example 3
[0098] This embodiment provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, and a preparation method thereof includes:
[0099] Preparing anhydride-modified partially carboxyl-terminated polyester polyol in advance, and then preparing isocyanate-terminated polyurethane prepolymer, wherein the isocyanate-terminated prepolymer and each raw material are calculated by mass fraction;
[0100] (1) Preparing an anhydride-modified partially carboxyl-terminated polyester polyol, comprising: taking succinic anhydride and poly (hexanediol dimer acid-polyneopentyl sebacate) ester with a molecular weight of 2000-3000, adding them in a ratio of 1:20 between the anhydride and the hydroxyl group in the hydroxyl-terminated polyester polyol, heating the polyester polyol and the anhydride to 100° C., stirring for 6 hours, until the error between the hydroxyl value and the acid value of chemical titration is less than 5% from the theoretical value, terminating the reaction, and cooling to room temperature to obtain an anhydride-modified partially carboxyl-terminated polyester polyol.
[0101] (2) Take 50 parts of anhydride-modified partially carboxyl-terminated polyester polyol, stir and heat to 120°C, maintain vacuum to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 50 parts of isophorone diisocyanate, slowly heat to 85°C, stir to react for 5 hours, and cool to room temperature to obtain a terminal isocyanate prepolymer.
[0102] Then, component A and component B are prepared respectively, wherein each raw material in component A and component B is calculated by weight;
[0103] (3) Preparation of component A: 38 parts of castor oil, 12 parts of aromatic ring-modified castor oil, 4 parts of bisphenol F-modified polyol, 8 parts of aromatic ring-containing polyether polyol, 1.0 part of KH560, 0.1 part of 1,2-dimethylimidazole, 30 parts of aluminum hydroxide, 5 parts of molecular sieves, 1.5 parts of fumed silica, and 0.5 part of 1076 were dispersed and stirred evenly, and component A was obtained after stirring for 3 hours;
[0104] (4) Preparation of component B: 68 parts of terminal isocyanate prepolymer, 32 parts of aluminum hydroxide, 0.5 parts of p-toluenesulfonyl isocyanate, 1.5 parts of fumed silica, and 0.5 parts of polycarbodiimide were taken, and stirred for 3 hours to obtain component B;
[0105] (5) The component A and the component B prepared above are combined in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0106] Example 4
[0107] This embodiment provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, and a preparation method thereof includes:
[0108] Preparing anhydride-modified partially carboxyl-terminated polyester polyol in advance, and then preparing isocyanate-terminated polyurethane prepolymer, wherein the isocyanate-terminated prepolymer and each raw material are calculated by mass fraction;
[0109] (1) Preparing an anhydride-modified partially carboxyl-terminated polyester polyol, comprising: taking glutaric anhydride and poly(hexamethylene dimer) with a molecular weight of 2000-3000, adding them in a ratio of 1:10 between the anhydride and the hydroxyl group in the hydroxyl-terminated polyester polyol, heating the polyester polyol and the anhydride to 150° C., stirring for 4 hours, until the error between the chemical titration result of the hydroxyl value and the acid value and the theoretical value is less than 5%, terminating the reaction, and cooling to room temperature to obtain an anhydride-modified partially carboxyl-terminated polyester polyol.
[0110] (2) Take 50 parts of anhydride-modified partially carboxyl-terminated polyester polyol, stir and heat to 120°C, maintain vacuum to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 50 parts of liquefied MDI, slowly heat to 80°C, stir to react for 2.5 hours, and cool to room temperature to obtain a terminal isocyanate prepolymer.
[0111] Then, component A and component B are prepared respectively, wherein each raw material in component A and component B is calculated by weight;
[0112] (3) Preparation of component A: 28 parts of castor oil, 10 parts of palm oil, 8 parts of bisphenol A modified polyol, 12 parts of polyether polyol containing aromatic ring, 1.0 part of KH560, 0.1 part of N,N-dimethylcyclohexylamine, 30 parts of aluminum hypophosphite, 5 parts of molecular sieves, 1.5 parts of fumed silica, and 0.5 part of 1135 were dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0113] (4) Preparation of component B: 70 parts of isocyanate-terminated prepolymer, 30 parts of aluminum hypophosphite, 0.5 parts of p-toluenesulfonyl isocyanate, 1.5 parts of fumed silica, and 0.5 parts of polycarbodiimide were taken, and stirred for 2.5 hours to obtain component B;
[0114] (5) The component A and the component B prepared above are combined in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0115] Example 5
[0116] This embodiment provides a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, and a preparation method thereof includes:
[0117] Preparing anhydride-modified partially carboxyl-terminated polyester polyol in advance, and then preparing isocyanate-terminated polyurethane prepolymer, wherein the isocyanate-terminated prepolymer and each raw material are calculated by mass fraction;
[0118] (1) Preparing an anhydride-modified partially carboxyl-terminated polyester polyol, comprising: taking maleic anhydride and poly(hexanediol succinate) having a molecular weight of 2000-3000, adding them in a molar ratio of anhydride to hydroxyl groups in the hydroxyl-terminated polyester polyol of 1:10, heating the polyester polyol and the anhydride to 100° C., stirring for 4 hours, until the chemical titration results of the hydroxyl value and the acid value are less than 5% of the theoretical error, terminating the reaction, and cooling to room temperature to obtain an anhydride-modified partially carboxyl-terminated polyester polyol.
[0119] (2) Take 40 parts of anhydride-modified partially carboxyl-terminated polyester polyol, stir and heat to 120°C, maintain vacuum to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 60 parts of dicyclohexylmethane diisocyanate, slowly heat to 80°C, stir to react for 3 hours, and cool to room temperature to obtain a terminal isocyanate prepolymer.
[0120] Then, component A and component B are prepared respectively, wherein each raw material in component A and component B is calculated by weight;
[0121] (3) Preparation of component A: 30 parts of castor oil, 10 parts of hydrogenated castor oil, 8 parts of bisphenol A modified polyol, 14 parts of polyether polyol containing aromatic ring, 1.0 part of KH560, 0.1 part of N,N-dimethylcyclohexylamine, 30 parts of aluminum hypophosphite, 5 parts of molecular sieves, 1.5 parts of fumed silica, and 0.5 part of 1135 were dispersed and stirred evenly, and component A was obtained after stirring for 2.5 hours;
[0122] (4) Preparation of component B: 60 parts of isocyanate-terminated prepolymer, 38 parts of aluminum hypophosphite, 0.5 parts of p-toluenesulfonyl isocyanate, 1.5 parts of fumed silica, and 0.5 parts of polycarbodiimide were taken, and stirred for 2 hours to obtain component B;
[0123] (5) The component A and the component B prepared above are combined in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
[0124] The long-shelf-life high-strength two-component polyurethane structural adhesive for power batteries prepared in the above embodiments was tested for tensile strength, shear strength, B component opening time, flame retardancy at 25°C, tensile strength and shear strength after double 85 aging for 1000h, storage stability at 50°C for 60 days simulating sea transportation, and storage stability at room temperature of 25°C for 18 months. Untreated aluminum alloy and PET were used as the substrate.
[0125] Table 1 is the performance test data of the two-component polyurethane structural adhesive of each embodiment
[0126]
[0127]
[0128] Note: In Table 1 above, A represents component A and B represents component B.
[0129] It can be seen from the test data in Table 1 above that the two-component polyurethane structural adhesive for high-strength power batteries with a long shelf life of the present invention has a long open time of component B, and the open time of component B under standard conditions is ≥15h. It has good storage stability at 50°C for 60 days and 25°C for 18 months, and has excellent tensile strength. It has excellent shear strength for untreated Al and PET, and the flame retardant performance can reach the flame retardant level. After double 85 aging for 1000h, the attenuation is less than 20%, which can effectively ensure the performance stability of the power battery during long-term use in complex environments such as high-frequency vibration, damp heat, severe cold, extreme heat, heat accumulation, etc., as well as the stability during transportation and storage, thereby improving reliability and safety.
[0130] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. The information disclosed in the background technology section of this article is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as an admission or in any form that the information constitutes prior art known to those skilled in the art.
Claims
1. A two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life, characterized in that: include: Component A and component B, the functional group molar ratio of component A to component B is: NCO:OH=1.05:1-2.0:1, and the component A and component B are mixed in a volume ratio of 1:1; wherein, The component A is composed of the following raw materials in parts by mass: 20-40 parts of a first bio-based polyol, 5-15 parts of a second bio-based polyol, 2-30 parts of an aromatic ring-modified polyol, 5-20 parts of an aromatic ring-containing polyether polyol, 0.5-1.5 parts of a coupling agent, 0.01-0.5 parts of a catalyst, 10-40 parts of a flame retardant, 2-10 parts of a water scavenger, 0.1-0.5 parts of an antioxidant, and 0.5-5 parts of a thixotropic agent; The B component is composed of the following raw materials in parts by mass: 60-85 parts of terminal isocyanate polyurethane prepolymer, 10-40 parts of flame retardant, 0.5-5 parts of thixotropic agent, 0.1-0.5 parts of dehydrating agent and 0.1-1 parts of anti-hydrolysis agent.
2. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 1, characterized in that: In the component A, the first bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic ring-modified castor oil; The second bio-based polyol is one or more of soybean oil, castor oil, palm oil, hydrogenated castor oil, and aromatic ring-modified castor oil; The aromatic ring modified polyol is one or more of bisphenol A or bisphenol F modified polyether diol and phthalic anhydride polyester diol with a molecular weight of 400 to 3000; The hydroxyl value of the aromatic ring-containing polyether polyol is 150 mg KOH / g to 450 mg KOH / g; The coupling agent is one or more of silane coupling agents KH550, KH560, KH570, KH580, and KH792; The catalyst is one or more of N,N-dimethylcyclohexylamine, triethylenediamine, 1,2-dimethylimidazole, N-ethylmorpholine, N-methylmorpholine, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth naphthenate, zinc isooctanoate, zinc neodecanoate, dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, and chelated tin; The dehydrating agent is one or more of molecular sieve, calcium chloride and aluminum sulfate; The antioxidant is one or more of 1076, 1010, 1135 and 245.
3. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 1 or 2, characterized in that: In the B component, the isocyanate-terminated polyurethane prepolymer is produced by reacting an anhydride-modified partially carboxyl-terminated polyester polyol with a molecular weight of 500-4000 with isocyanate, and the mass fraction of NCO is controlled to be 5-20%.
4. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 3, characterized in that: In the isocyanate-terminated polyurethane prepolymer, the isocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and liquefied MDI; The anhydride-modified partially carboxyl-terminated polyester polyol is a polyester polyol synthesized from a diacid monomer and a polyol monomer.
5. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 4, characterized in that: In the acid anhydride-modified partially carboxyl-terminated polyester polyol, the diacid monomer is one or more of hydrogenated dimer acid, dimer acid, succinic acid, adipic acid, sebacic acid, terephthalic acid, isophthalic acid, and phthalic anhydride; The acid anhydride is one or more of maleic anhydride, succinic anhydride, glutaric anhydride, phthalic anhydride, tetrahydrophthalic anhydride, bromotetrahydrophthalic anhydride, and hexahydrophthalic anhydride; The polyol monomer is one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,10-decanediol, glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
6. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 1 or 2, characterized in that: In the B component, the anti-hydrolysis agent is polycarbodiimide; The dewatering agent is p-toluenesulfonyl isocyanate.
7. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 1 or 2, characterized in that: In the component A and the component B, the thixotropic agent is one or more of fumed silica and bentonite; In the component A and the component B, the flame retardant is a solid flame retardant or a liquid flame retardant.
8. The two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to claim 7, characterized in that: The solid flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, and diethyl aluminum phosphite; The liquid flame retardant is one or more of tricresyl phosphate, triethyl phosphate, and tri(chloroisopropyl) phosphate.
9. A method for preparing the two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the formula of component A and component B described in any one of claims 1 to 8, the constituent raw materials of component A and component B are respectively taken, and the raw materials of component A and component B are respectively mixed evenly to obtain component A and component B, and the prepared component A and component B are combined and used in a volume ratio of 1:1 to obtain a two-component polyurethane structural adhesive for power batteries with a long shelf life and high strength.
10. The method for preparing a two-component polyurethane structural adhesive for a high-strength power battery with a long shelf life according to claim 9, characterized in that: The isocyanate-terminated polyurethane prepolymer in the B component is prepared in the following manner, including: First, prepare anhydride-modified partially carboxyl-terminated polyester polyol as follows: Adding polyester polyol and acid anhydride into a reaction container, adding in a molar ratio of acid anhydride to hydroxyl group in terminal hydroxyl polyester polyol of 1:100 to 1:5, heating polyester polyol and acid anhydride to 100-200° C., stirring for 2-6 hours, until the chemical titration result of hydroxyl value and acid value is less than 5% of the theoretical error, ending the reaction, cooling to room temperature, and obtaining acid anhydride-modified partially carboxyl-terminated polyester polyol; The isocyanate-terminated prepolymer is then prepared in the following manner, comprising: The anhydride-modified partially carboxyl-terminated polyester polyol is heated to 110-120° C., stirred and vacuumed, dehydrated for 1-3 hours, cooled to below 50° C., filled with nitrogen, and isocyanate is added in a ratio of 5-20% of the theoretical NCO content. The temperature is raised to 65-85° C., stirred and reacted for 1-5 hours until the titrated NCO content no longer changes to terminate the reaction, and cooled to room temperature to obtain an isocyanate-terminated prepolymer.
Citation Information
Cited By
Detachable polyurethane structural adhesive with high initial strength as well as preparation method and application thereof
CN119955459A